A Comparative Study on the Performance of LLR- and SNR-Based Hybrid Relaying Schemes - El-Mahdy, Ahmed; Alexan, Wassim (Wireless Communications and Mobile Computing, 2017)
A comparative study on the theoretical bit error rate (BER) is presented for hybrid relaying schemes that toggle between adaptive decode-and-forward (ADF) and amplify-and-forward (AF) protocols, for a typical three-node wireless network. Toggling between the two forwarding protocols is based on the log-likelihood ratio (LLR) or the signal-to-noise ratio (SNR) of the received signal at the relay node. Closed-form expressions for the probability of error are presented, as well as the expressions of the proposed schemes’ gains over classical ADF and AF protocols. Comparisons are carried out among the two schemes and other hybrid schemes found in the literature. Moreover, the impact of relay location on the probability of error is investigated.